Variable recruitment in bundles of miniature pneumatic artificial muscles. (13th September 2016) - DeLaHunt, Sylvie A; Pillsbury, Thomas E; Wereley, Norman M
Abstract: The natural compliance and force generation properties of pneumatic artificial muscles (PAMs) allow them to operate like human muscles in anthropomorphic robotic manipulators. Traditionally, manipulators use a single PAM or multiple PAMs actuated in unison in place of a human muscle. However, these standard manipulators can experience significant efficiency losses when operated outside their target performance ranges at low actuation pressures. This study considers the application of a variable recruitment control strategy to a parallel bundle of miniature PAMs as an attempt to mimic the selective recruitment of motor units in a human muscle. Bundles of miniature PAMs are experimentally characterized, their actuation behavior is modeled, and the efficiency gains and losses associated with the application of a variable recruitment control strategy are assessed. This bio-inspired control strategy allows muscle bundles to operate the fewest miniature PAMs necessary to achieve a desired performance objective, improving the muscle bundle's operating efficiency over larger ranges of force generation and displacement. The study also highlights the need for improved PAM fabrication techniques to facilitate the production of identical miniature PAMs for inclusion in muscle bundles.